2002
DOI: 10.1007/s00381-002-0607-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of thalamic tumors in children

Abstract: In the present paper we have focused attention on the neuroimaging features of thalamic tumors in a pediatric population; based upon personal experience, we suggest a rational neuroradiological approach to the diagnostic evaluation, describe CT and MRI findings of the most common tumors, and attempt to define basic patterns in order to provide the most reliable "pathological" diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…However, we showed that children with GC commonly have involvement of deeper brain structures, including the thalami. Furthermore, similar to other studies in children [1, 5, 6], we showed that more than 25 % of our patients had symmetrical bithalamic involvement as a prominent feature of GC. Because only 4 of our 9 patients with GC and a symmetrical bithalamic involvement had molecular data available, the possibility that a H3F3A p.K27M mutation could be found in pediatric GC cannot be entirely excluded.…”
Section: Discussionsupporting
confidence: 92%
“…However, we showed that children with GC commonly have involvement of deeper brain structures, including the thalami. Furthermore, similar to other studies in children [1, 5, 6], we showed that more than 25 % of our patients had symmetrical bithalamic involvement as a prominent feature of GC. Because only 4 of our 9 patients with GC and a symmetrical bithalamic involvement had molecular data available, the possibility that a H3F3A p.K27M mutation could be found in pediatric GC cannot be entirely excluded.…”
Section: Discussionsupporting
confidence: 92%
“…It has been hypothesized that these symptoms arise due to the impairment of the dorsomedial nuclei, which have connections to the amygdala, the temporal neocortex, and the prefrontal region [24]. Most cases of bilateral thalamic astrocytomas occur in children [25]. These patients nearly always need a shunt because of compression of the third ventricle caused by the tumor (Figure 7).…”
Section: Tumormentioning
confidence: 99%
“…Bilateral diffuse thalamic gliomas on MRS show an elevated creatinine peak compared to choline [20]; however, whether this finding is characteristic of the bilateral manifestation is still controversial [21]. An increase in choline can itself serve as a measure of the proliferation activity of the tumor, since it correlates with the membrane metabolism [25].…”
Section: Tumormentioning
confidence: 99%
“…At present, tumours arising in the brainstem, known as diffuse intrinsic pontine glioma (DIPG), have been extensively investigated and stratified into disease subtypes [6, 20]. Whereas DIPG is heavily researched, thalamic tumours, accounting for approximately 5 % of all paediatric brain neoplasms, are largely unexplored [810, 14, 27, 28]. Currently, the outcome of patients with thalamic tumours is predicted based on the histological grade and the potential for surgical resection of the tumour.…”
Section: Introductionmentioning
confidence: 99%